Method for extracting lithium from surface shell material and overhaul slag and co-producing steel mill slagging agent

By repeatedly processing the shell material and overhaul slag, separating carbon powder by flotation and extracting lithium by acid leaching, the problem of low lithium resource recovery efficiency in existing technologies is solved, realizing efficient lithium recovery and high-value utilization of resources, and reducing environmental pollution and production costs.

CN119287164AActive Publication Date: 2025-01-10河南新天力循环科技有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411498094.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Existing technologies are insufficient for the efficient recovery of lithium resources from waste materials in the electrolytic aluminum industry, especially surface materials and overhaul slag, and the process also involves resource waste and environmental pollution.

Method used

The carbon powder is separated by flotation after the shell material and overhaul slag are ground into fine powder using a multiple-cycle method. Then, lithium is extracted by acid leaching and multiple pH adjustments. Finally, a slag-reducing agent is prepared and industrial-grade lithium carbonate is synthesized.

Benefits of technology

This has enabled efficient lithium recovery and high-value utilization of resources, reduced the generation of waste liquid and slag, and lowered the production costs of steel enterprises.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287164A_ABST
    Figure CN119287164A_ABST
Patent Text Reader

Abstract

The invention provides a method for extracting lithium from a surface shell material and overhaul slag and co-producing a steel mill slagging agent, which comprises the following steps: mixing and grinding the surface shell material and the overhaul slag, then carrying out acid leaching, carrying out secondary leaching and stirring washing on the leached slag to obtain residues, and carrying out ball pressing and drying on the residues, limestone and a binder to produce the slagging agent, removing impurities from the leachate, adsorbing and enriching lithium by using an adsorbing material, and performing high-temperature and high-pressure desorption, cooling and membrane concentration on lithium-enriched slag to finally synthesize an industrial-grade lithium carbonate product; according to the method, the metal lithium is efficiently recycled, meanwhile, the tailings are produced into the slag melting agent used in the steel mill, high-value utilization is achieved, and no waste water or waste residue is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of comprehensive utilization of waste resources in the electrolytic aluminum industry, and in particular to a method for extracting lithium from shell material and overhaul slag and co-producing a slag-reducing agent for a steel plant. Background Art

[0002] With the widespread use of electronic products such as electric vehicles and smartphones, lithium has become increasingly popular as an important battery material. With the decline in the price of lithium carbonate, the recovery of lithium from battery waste is at a loss, and the various waste slags produced during the aluminum smelting process contain a large amount of lithium, which is an important source of lithium and is attracting more and more attention from practitioners.

[0003] When aluminum is produced industrially by cryolite-alumina molten salt electrolysis, the waste aluminum electrolyte usually contains a high level of lithium. The reason is that the raw material alumina for electrolytic aluminum contains Li2O to varying degrees. During the electrolysis process, lithium enters the electrolyte in the form of ions. As the age of the electrolytic cell increases, lithium is continuously enriched. When the lithium element in the aluminum electrolyte reaches 2-3% by mass in terms of LiF, it helps to reduce the initial crystallization temperature of the electrolyte and reduce energy consumption; however, when the lithium content in the aluminum electrolyte is too high, the electrolyte system will not only reduce the solubility of alumina in the electrolyte, but also cause the electrolyte to overheat, increase energy consumption, shorten the service life of the electrolytic cell, and affect the economic benefits of electrolytic aluminum. Therefore, when the lithium content in the aluminum electrolyte is too high, the aluminum electrolyte needs to be replaced regularly, and the replaced aluminum electrolyte is the waste aluminum electrolyte.

[0004] The shell material is the aluminum oxide crust on the top of the anode of the electrolytic cell. The shell material has the functions of heat preservation and anti-oxidation. It can be repeatedly used in the electrolytic production process after being crushed. Some electrolytes will cover the anode residues during the anode electrolysis process. Therefore, the shell material is a physical mixture of aluminum oxide and electrolyte, which contains impurity elements such as carbon, calcium, silicon and iron in addition to elements such as fluorine, aluminum, sodium and lithium.

[0005] The service life of the electrolytic cells used in aluminum electrolysis is generally 3 to 5 years. The waste formed by the electrolytic cells that are replaced during equipment maintenance is collectively referred to as aluminum electrolytic cell overhaul slag. Usually, 20 to 30 kg of overhaul slag is produced for every ton of aluminum produced. Overhaul slag can generally be divided into waste refractory materials, waste cathode carbon materials and mixed materials. It not only contains valuable elements such as Li and Al, but also rich in highly toxic fluorides and cyanides. According to the standard, the amount of fluoride and cyanide in the overhaul slag leachate can reach about 2500 and 5 mg / L respectively, far exceeding the safety values ​​specified in the standard. Effectively recovering the lithium resources can not only turn waste into treasure to alleviate the shortage of lithium resources, but also reduce the pollution of waste slag to the environment.

[0006] Data shows that my country's aluminum electrolysis industry produces more than one million tons of excess waste aluminum electrolyte and overhaul slag every year. The relatively pure electrolyte is processed into regenerated cryolite or aluminum fluoride after lithium extraction and then used in the aluminum smelting industry. For example, CN114438329A discloses a comprehensive recovery method for waste lithium-aluminum electrolyte. First, the lithium-aluminum electrolyte is crushed and finely ground into 100-400 mesh electrolyte powder; acid solution is prepared and leaching enhancer is added, and then the electrolyte powder is added to the acid solution for leaching and filtering, and the filter residue is washed and dried to obtain the sub-cryolite product. However, shell materials and overhaul slag are not efficiently utilized due to their complex composition and many impurities, high carbon content and relatively low available fluorine content, and lithium content not as high as the electrolyte. After leaching, the lithium concentration in the solution is low, and some of them are landfilled after harmless treatment, resulting in waste of resources, or have problems such as long process routes and high production costs. Because a large amount of auxiliary materials will be consumed in the removal of impurities in solutions with low lithium and high impurities, and the lithium entrainment loss is large, secondly, the lithium-containing solution after impurities removal is often only about 2g / L or even lower, and a large amount of crystalline salt will precipitate during evaporation and concentration, and the entrainment loss of lithium in the salt is very large. Finally, when the concentrated solution is synthesized, only crude lithium carbonate can be obtained due to the high impurities.

[0007] CN 115846377 A discloses harmless electrolytic aluminum overhaul slag, its application and harmless method for electrolytic aluminum overhaul slag, which is treated to meet the standards and reach the conditions for entry into a flexible landfill. The method does not recover lithium and does not make high-value use of the overhaul slag.

[0008] CN 118125481 A discloses a method for treating electrolytic aluminum carbon slag, firstly, the electrolytic aluminum carbon slag is roasted at 1200℃ to burn the carbon in the electrolytic aluminum carbon slag to obtain lithium-rich smoke and lithium-rich electrolyte; then, the lithium-rich electrolyte is activated by sulfuric acid to obtain defluorinated lithium-rich electrolyte slurry and hydrogen fluoride gas; after solid-liquid separation of the defluorinated lithium-rich electrolyte slurry, lithium-rich electrolyte filtrate and lithium-rich electrolyte filter cake are obtained, and the lithium-rich electrolyte filter cake is heated, leached and solid-liquid separated to obtain aluminum fluoride filter cake. This route has high energy consumption for high-temperature roasting, and the synthesis of aluminum fluoride first and then lithium extraction will inevitably cause lithium entrainment loss.

[0009] Therefore, it is urgent to develop a method with short process, high yield and high added value of tailings, which can simultaneously process shell material and overhaul slag without generating wastewater and waste slag. Summary of the invention

[0010] The purpose of the present invention is to address the deficiencies of the above-mentioned prior art and provide a method for extracting lithium from shell material and overhaul slag and co-producing a slag-reducing agent for a steel plant.

[0011] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for extracting lithium from surface shell material and overhaul slag and co-producing a slag-reducing agent for a steel plant, comprising N consecutive cycles and the following steps: S1. Grind the overhaul slag into powder of 100-200 mesh, add flotation agent to float and separate carbon powder; Grind the shell material into powder of 100-200 mesh, mix it with the overhaul slag after flotation, and acid leaching. The mixing ratio of shell material to overhaul slag is 1: (0-2); S2, mixing the mixed raw material with the second solution to prepare a slurry, wherein the mass volume ratio of the raw material to the second solution is 1:(1-3), then, adding 4%-10% of a leaching aid, a cyanide destroying agent and a leaching agent by mass ratio, maintaining the system pH at 0.5-1.5, and stirring the reaction at 70°C-100°C for 1-4 hours; S3, after the end of S2, the fourth solid material is pumped in, and the ratio of the fourth solid material to the mixture of the shell material and the overhaul slag is (0.1-0.3) by mass ratio: 1, the pH is adjusted to 2-4, and after stabilization for 30-60 minutes, the slurry is filtered to obtain a first filtrate and a first filter residue; If the lithium content of the first filter residue is less than 0.1%, the step S4 is omitted; S4, the first filtrate is subjected to secondary leaching with the third solution, the liquid-to-solid ratio is controlled to be 1.5-3:1 by mass ratio, the pH is adjusted to 1-2 by industrial hydrochloric acid or sulfuric acid, the reaction is carried out at 50°C-80°C for 1h-2h, and the second filtrate and the second filter residue are obtained by filter pressing; S5, adjusting and stirring the second filter residue with the fifth solution, controlling the liquid-to-solid ratio to be 1.5-3:1 by mass ratio, washing at room temperature for 30-60 minutes, and obtaining a third filtrate and a third filter residue after filter pressing; S6. Mix the third filter residue, aggregate and adhesive in a mass ratio of 100:5~20:1~5, and prepare a slag-removing agent product after ball pressing and drying.

[0012] Furthermore, it also includes: S7, adding the first filtrate and alkali solution into a decontamination tank, controlling the pH value to 5-8 and the temperature to 40°C-80°C, so that the impurity elements in the solution are precipitated, stirring the reaction for 1h and filtering to obtain a fourth filtrate and a fourth filter residue; S8. Use liquid alkali to completely dissolve the sixth solid material and / or aluminum hydroxide to obtain a sodium aluminate solution, and use hydrochloric acid or sulfuric acid and / or aluminum hydroxide to completely dissolve to obtain an aluminum chloride solution or an aluminum sulfate solution; add the sodium aluminate solution and the aluminum chloride solution or the aluminum sulfate solution to the fourth filtrate, control the pH value during the process to 9-10, control the endpoint pH value to 6-8, and the temperature to 80°C-100°C. After stabilizing for 1h-3h, filter by pressure to obtain a fifth filtrate and a fifth filter residue; the fifth filter residue is a lithium-rich residue with a lithium content greater than 4%.

[0013] Furthermore, it also includes: S9. The fifth filter residue is slurried with pure water to a liquid-to-solid ratio of 10-30:1, and is subjected to high temperature and high pressure analysis at 200°C-250°C for 1h-3h. After filtration, a sixth filtrate and a sixth filter residue are obtained. The sixth filter residue and pure water are subjected to multi-stage plate exchange and circulating water cooling, and a lithium-rich concentrate is obtained after membrane concentration, which is then synthesized to obtain industrial-grade lithium carbonate.

[0014] Furthermore, in said S1, the mixing ratio of the ground flour shell material and the overhaul slag after flotation is, by mass ratio, that after mixing, the fluorine content is greater than 26% to 36%, and the carbon content is 5% to 15%; When the carbon content in the ground flour shell material and the overhaul slag after flotation is less than 15%, the overhaul slag does not need to be flotated to separate the carbon powder.

[0015] Furthermore, the flotation agent is a general term for foaming agent, inhibitor and collector; the foaming agent is No. 2 oil or ether alcohol; the inhibitor is water glass; and the collector is kerosene.

[0016] Further, in said S2, The leaching aid is aluminum oxide or aluminum hydroxide. After the leaching aid is added, the molar ratio of fluorine to aluminum in the mixed slurry is controlled between 2 and 3:1; The leaching agent is industrial hydrochloric acid or sulfuric acid; If the cyanide-breaking agent is a hydrochloric acid system, sodium chlorate or sodium hypochlorite is selected; if the cyanide-breaking agent is a sulfuric acid system, hydrogen peroxide is selected. The addition ratio is 0-2% of the weight of the shell material and overhaul slag, and cyanide is converted into non-toxic nitrogen and carbon dioxide.

[0017] Further, it is characterized in that: When N is 1, The second solution and the third solution are tap water; the fifth solution is tap water; The first solid material is not added; the sixth solid material is aluminum hydroxide; When N is greater than 1, The second solution is the second filtrate; the third solution is the third filtrate; the fifth solution is the fifth filtrate; The fourth solid material is the fourth filter residue; the sixth solid material is the sixth filter residue.

[0018] The beneficial effects of the present invention are as follows: the present invention combines the surface shell material and the hazardous waste residues such as the overhaul residue for treatment, adopts the adsorption enrichment of lithium instead of the traditional impurity removal method to solve the problem of low lithium content and high impurities in the leachate, and obtains industrial-grade lithium carbonate after the lithium-rich material is analyzed, and the leached residue is made into a slag-removing agent used in steel mills. China's annual steel production reaches 1 billion tons, and the slag-removing dosage per ton of steel is about 2‰, which has a huge market and can effectively reduce the production cost of steel enterprises. The entire treatment process is short, the lithium recovery rate is high, and no waste liquid and waste residue are generated in the whole process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a method for extracting lithium from surface shell material and overhaul slag and co-producing slag-reducing agent for steel plant. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0021] See also Figure 1 A method for extracting lithium from shell material and overhaul slag and co-producing steel mill slag reducing agent comprises N consecutive cycles and the following steps: S1. Grind the overhaul slag into powder of 100-200 mesh, add flotation agent to float and separate carbon powder; Grind the shell material into powder of 100-200 mesh, mix it with the overhaul slag after flotation, and acid leaching. The mixing ratio of shell material to overhaul slag is 1: (0-2); S2, mixing the mixed raw material with the second solution to prepare a slurry, wherein the mass volume ratio of the raw material to the second solution is 1:(1-3), then, adding 4%-10% of a leaching aid, a cyanide destroying agent and a leaching agent by mass ratio, maintaining the system pH at 0.5-1.5, and stirring the reaction at 70°C-100°C for 1-4 hours; S3, after the end of S2, the fourth solid material is pumped in, and the ratio of the fourth solid material to the mixture of the shell material and the overhaul slag is (0.1-0.3) by mass ratio: 1, the pH is adjusted to 2-4, and after stabilization for 30-60 minutes, the slurry is filtered to obtain a first filtrate and a first filter residue; If the lithium content of the first filter residue is less than 0.1%, the step S4 is omitted; S4, the first filtrate is subjected to secondary leaching with the third solution, the liquid-to-solid ratio is controlled to be 1.5-3:1 by mass ratio, the pH is adjusted to 1-2 by industrial hydrochloric acid or sulfuric acid, the reaction is carried out at 50°C-80°C for 1h-2h, and the second filtrate and the second filter residue are obtained by filter pressing; S5, adjusting and stirring the second filter residue with the fifth solution, controlling the liquid-to-solid ratio to be 1.5-3:1 by mass ratio, washing at room temperature for 30-60 minutes, and obtaining a third filtrate and a third filter residue after filter pressing; S6. Mix the third filter residue, aggregate and adhesive in a mass ratio of 100:5~20:1~5, and prepare a slag-removing agent product after ball pressing and drying.

[0022] Also includes: S7, adding the first filtrate and alkali solution into a decontamination tank, controlling the pH value to 5-8 and the temperature to 40°C-80°C, so that the impurity elements in the solution are precipitated, stirring the reaction for 1h and filtering to obtain a fourth filtrate and a fourth filter residue; S8. Use liquid alkali to completely dissolve the sixth solid material and / or aluminum hydroxide to obtain a sodium aluminate solution, and use hydrochloric acid or sulfuric acid and / or aluminum hydroxide to completely dissolve to obtain an aluminum chloride solution or an aluminum sulfate solution; add the sodium aluminate solution and the aluminum chloride solution or the aluminum sulfate solution to the fourth filtrate, control the pH value during the process to 9-10, control the endpoint pH value to 6-8, and the temperature to 80°C-100°C. After stabilizing for 1h-3h, filter by pressure to obtain a fifth filtrate and a fifth filter residue; the fifth filter residue is a lithium-rich residue with a lithium content greater than 4%.

[0023] Also includes: S9. The fifth filter residue is slurried with pure water to a liquid-to-solid ratio of 10-30:1, and is subjected to high temperature and high pressure analysis at 200°C-250°C for 1h-3h. After filtration, a sixth filtrate and a sixth filter residue are obtained. The sixth filter residue and pure water are subjected to multi-stage plate exchange and circulating water cooling, and a lithium-rich concentrate is obtained after membrane concentration, which is then synthesized to obtain industrial-grade lithium carbonate.

[0024] In S1, the mixing ratio of the ground flour shell material and the overhaul slag after flotation is, by mass ratio, fluorine is greater than 26% to 36% and carbon is 5% to 15% after mixing; When the carbon content in the ground flour shell material and the overhaul slag after flotation is less than 15%, the overhaul slag does not need to be flotated to separate the carbon powder.

[0025] The flotation agent is a general term for foaming agent, inhibitor and collector; the foaming agent is No. 2 oil or ether alcohol; the inhibitor is water glass; and the collector is kerosene.

[0026] In S2, The leaching aid is aluminum oxide or aluminum hydroxide. After the leaching aid is added, the molar ratio of fluorine to aluminum in the mixed slurry is controlled between 2 and 3:1; The leaching agent is industrial hydrochloric acid or sulfuric acid; If the cyanide-breaking agent is a hydrochloric acid system, sodium chlorate or sodium hypochlorite is selected; if the cyanide-breaking agent is a sulfuric acid system, hydrogen peroxide is selected. The added ratio is 0-2% of the weight of the shell material and the overhaul slag. The cyanide is converted into non-toxic nitrogen and carbon dioxide.

[0027] When N is 1, The second solution and the third solution are tap water; the fifth solution is tap water; The fourth solid material is not added; the sixth solid material is aluminum hydroxide; When N is greater than 1, The second solution is the second filtrate; the third solution is the third filtrate; the fifth solution is the fifth filtrate; The fourth solid material is the fourth filter residue; the sixth solid material is the sixth filter residue.

[0028] Embodiment 1

[0029] S1. Grind the overhaul slag to less than 150 mesh, then add a flotation agent composed of No. 2 oil, water glass and kerosene to float and separate the carbon powder, and then sell the carbon powder after drying; Grind the shell material to less than 150 mesh, then mix the shell material and the overhaul slag after flotation for acid leaching, and the doping ratio of the shell material to the overhaul slag is 1:2; after mixing, the fluorine content is 28.8 and the carbon content is 6.5%; Shell material: lithium 1.2%, silicon dioxide 0.65%, calcium oxide 3.2%, aluminum oxide 18.5%, sodium oxide 24.8%, fluorine 33.5%, carbon 3.5%; Overhaul slag: lithium 0.85%, fluoride 26.8%, cyanide 0.22%, aluminum nitride 2.5%, aluminum carbide 3.8%, carbon 22.5%; S2, 10 tons of mixed raw materials and 20 cubic meters of the second filtrate were mixed and slurried, and then 1 ton of aluminum hydroxide was added, and then 10 kg of sodium chlorate solid powder was added, and then 5.3 tons of industrial hydrochloric acid was added to adjust the pH to 1.1, and the reaction was stirred at 90 ° C for 3 hours; S3, after S2 is completed, 5 cubic meters of the fourth filter residue is pumped in, the pH of the slurry is adjusted to 3.2, and after stabilization for 30 minutes, the slurry is filtered to obtain the first filtrate and the first filter residue. The lithium content in the first filtrate is 4.1 g / L, and the lithium content in the first filter residue is 0.36%; S4. The first filter residue is subjected to secondary leaching with the third filtrate, with a liquid-to-solid ratio of 2:1 by mass ratio, and the pH is adjusted to 1.2 with industrial hydrochloric acid, and the reaction is carried out at 80°C for 1 hour, and the second filtrate and the second filter residue are obtained by filter pressing, and the lithium content in the second filter residue is 0.22%; the secondary leaching adopts high acid leaching, and the leaching liquid is used as the primary leaching bottom liquid. The higher pH of the primary leaching can reduce the impurity content in the leaching liquid, and effectively reduce the alkali consumption in the impurity removal process; S5, the second filter residue is adjusted and stirred with the fifth filtrate, the liquid-to-solid ratio is controlled to be 2:1 by mass ratio, and washed at room temperature for 60 minutes, and the third filtrate and the third filter residue are obtained after pressure filtration, and the third filter residue contains 0.03% lithium; S6, the third filter residue is mixed with 5% limestone particles and 1% organic lignin paste binder, and after mixing, it is pressed into 10╳25mm elliptical balls by a ball press, and then dried by a dryer and packaged into a slag dissolving agent product with a moisture content of 0.2%; S7, the first filtrate and 32% liquid caustic soda are added to the impurity removal tank simultaneously, the process pH value is controlled to be 5-8, the end point pH is 6.5, the temperature is 80 ° C, the reaction is stirred for 1h and then filtered to obtain a fourth filtrate and a fourth filter residue, the fourth filter residue contains 0.8% lithium, and the third filtrate contains 3.1 g / L lithium; S8, using liquid alkali and the sixth filter residue to completely dissolve to obtain sodium aluminate solution, and using hydrochloric acid and aluminum hydroxide to completely dissolve to obtain aluminum chloride solution; heating the fourth filtrate to 90°C, and then adding the sodium aluminate solution and the aluminum chloride solution to the fourth filtrate in parallel, controlling the process pH to 9-10, and adding for 30 minutes to end, the end point pH is controlled to 7.5, and the temperature is continued to be stable at 90°C for 1 hour before filter pressing to obtain the fifth filtrate and the fifth filter residue; the residual lithium content in the fifth filtrate is 15 mg / L, and the fifth filter residue is lithium-rich residue with a lithium content of 4.2%; replacing the traditional process route of first removing impurities and then concentrating by adsorption enrichment of lithium, the liquid after adsorption is used for slurry preparation of impurity removal residue, and then returns to the first leaching process, after the impurities are enriched to a certain extent, the leaching of impurities will be inhibited, and there is no need to further concentrate the lithium-containing solution to produce crystalline salt; S9. The fifth filter residue is slurried with pure water at a liquid-to-solid ratio of 20:1, and the temperature is raised to 200°C for analysis for 1 hour. After filtration, the sixth filtrate and the sixth filter residue are obtained. The sixth filtrate contains 1.75 g / L lithium. After multi-stage plate heat exchange with pure water and circulating water cooling to 50°C, tertiary membrane concentration is performed to obtain a lithium-rich concentrated solution containing 20.5 g / L lithium. Then, sodium carbonate solution is added to synthesize industrial-grade lithium carbonate, and the main content of lithium carbonate is above 99.2%.

[0030] Embodiment 2

[0031] S1. Mix the shell material and the overhaul slag into a mill and grind them into a mixed raw material. The particle size is ground to less than 150 mesh. The mixing ratio of the two is 1:0.2. After mixing, the fluorine content is 32.5% and the carbon content is 6.8%; S2, 10 tons of mixed raw materials and 25 cubic meters of the second filtrate were mixed and slurried, and then 0.8 tons of aluminum oxide were added, and then 20 kg of industrial hydrogen peroxide solution was added, and then 3.4 tons of industrial sulfuric acid were added to adjust the pH to 1.0, and the reaction was stirred at 90 ° C for 4 hours; S3, after S2 is completed, 5 cubic meters of the fourth filter residue is pumped in, the pH of the slurry is adjusted to 3.5, and after stabilization for 30 minutes, the slurry is filtered to obtain the first filtrate and the first filter residue, and the lithium content of the first filter residue is 0.36%; S4, the first filter residue is subjected to secondary leaching with the third filtrate, the pH is adjusted to 1.5 by processing industrial sulfuric acid, the reaction is carried out at 80°C for 1 hour, and the second filtrate and the second filter residue are obtained by pressure filtration, and the lithium content in the second filter residue is 0.12%; S5, the second filter residue is adjusted and stirred with the fifth filtrate, the liquid-to-solid ratio is controlled at 2:1 by mass ratio, and washed at room temperature for 45 minutes, and the third filtrate and the third filter residue are obtained after filter pressing, and the third filter residue contains 0.06% lithium; S6. Mix the third filter residue with 8% calcite particles and 2% heavy oil, and press them into 10╳25mm elliptical balls through a ball press. Then, dry them in a dryer and package them into slag dissolving agent products with a moisture content of 0.25%; S7, adding the first filtrate and 32% liquid caustic soda simultaneously into the impurity removal tank, controlling the process pH value to 5-8, the end point pH to 7.0, stirring the reaction at 80°C for 1h and then filtering to obtain a fourth filtrate and a fourth filter residue, wherein the lithium content of the filter residue is 0.68%; S8, using liquid alkali and the sixth filter residue to completely dissolve to obtain sodium aluminate solution, and using industrial sulfuric acid and aluminum hydroxide to completely dissolve to obtain aluminum sulfate solution; heating the fourth filtrate to 90°C, and then adding the sodium aluminate solution and the aluminum sulfate solution to the fourth filtrate in parallel, controlling the process pH to 9-10, and adding for 40 minutes, the end point pH is controlled to 8.0, and the temperature is continued to be stable at 90°C for 1 hour and then filtered to obtain the fifth filtrate and the fifth filter residue; the residual lithium content in the fifth filtrate is 20.0 mg / L, and the fifth filter residue is lithium-rich residue with a lithium content of 4.45%; S9, the fifth filter residue is slurried with pure water, with a liquid-solid ratio of 25:1, heated to 220°C and analyzed for 2h, and filtered to obtain the sixth filtrate and the sixth filter residue. The sixth filtrate has a lithium content of 1.55g / L, and is subjected to multi-stage plate heat exchange with pure water and circulating water cooling to 55°C. After three-stage membrane concentration, a lithium-rich concentrated solution with a lithium content of 22.0g / L is obtained, and then sodium carbonate solution is added to synthesize industrial-grade lithium carbonate. The main content of lithium carbonate is above 99.2%, and it can be directly used as a raw material for low-end battery products without carbonization and purification; Embodiment 3

[0032] S1. Grind the overhaul slag to less than 150 mesh, then add a flotation agent composed of ether alcohol, water glass and kerosene to float and separate the carbon powder, and then sell the carbon powder after drying; Grind the shell material to less than 150 mesh, then mix the shell material with the overhaul slag after flotation for acid leaching, and the mixing ratio of the two is 1:1; after mixing, the fluorine content is 32.5% and the carbon content is 5.8%; S2, 10 tons of mixed raw materials and 25 cubic meters of the second filtrate were mixed and slurry mixed, and then 0.8 tons of aluminum hydroxide were added, followed by 15 kg of sodium hypochlorite solution, and then 4.8 tons of industrial hydrochloric acid were added to adjust the pH to 1.3, and the reaction was stirred at 95 ° C for 4 hours; S3, after S2 is completed, the fourth filter residue of 2 is pumped in, the pH of the slurry is adjusted to 2.5, and the slurry is filtered after stabilization for 30 minutes to obtain the first filtrate and the first filter residue, and the lithium content in the first filter residue is 0.08%; there is no secondary leaching step; S4, the first filter residue is adjusted and stirred with the fifth filtrate, the liquid-to-solid ratio is controlled at 2:1 by mass ratio, and the washing is carried out at room temperature for 60 minutes. After filter pressing, the third filtrate and the third filter residue are obtained, and the lithium content in the third filter residue is 0.04%; S6. Mix the third filter residue with 5% Baiyunshan granules and 4% boric acid, and press them into 10╳25mm elliptical balls through a ball press. Then, dry them in a dryer and package them into slag dissolving agent products with a moisture content of 0.2%; S7, adding the first filtrate and 32% liquid caustic soda simultaneously into the impurity removal tank, controlling the process pH value to be 5-8, the end point pH to be 8.0, stirring the reaction at 80°C for 1h and then filtering to obtain a fourth filtrate and a fourth filter residue, wherein the lithium content of the filter residue is 0.76%; S8, using liquid alkali and aluminum hydroxide to completely dissolve to obtain sodium aluminate solution, using hydrochloric acid and the sixth filter residue to completely dissolve to obtain aluminum chloride solution; heating the fourth filtrate to 92°C, then adding the sodium aluminate solution and the aluminum chloride solution to the fourth filtrate in parallel, controlling the process pH to 9-10, adding for 30 minutes, and controlling the end point pH to 8.0, continuing to stabilize at 92°C for 1 hour and then filtering to obtain the fifth filtrate and the fifth filter residue; the residual lithium content in the fifth filtrate is 12 mg / L, and the fifth filter residue is lithium-rich residue with a lithium content greater than 4.25%; S9. The fifth filter residue is slurried with pure water at a liquid-to-solid ratio of 22:1, and the temperature is raised to 250°C for analysis for 1.5 hours. After filtration, the sixth filtrate and the sixth filter residue are obtained. The sixth filtrate contains 1.66 g / L lithium. After multi-stage plate heat exchange with pure water and circulating water cooling to 60°C, tertiary membrane concentration is performed to obtain a lithium-rich concentrated solution containing 21.6 g / L lithium. Then, sodium carbonate solution is added to synthesize industrial-grade lithium carbonate, and the main content of lithium carbonate is above 99.2%.

[0033] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention should be based on the attached claims.

Claims

1. A method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel mills, characterized in that: It includes N consecutive loops and the following steps: S1. Grind the overhaul slag into powder of 100-200 mesh, add flotation agent to float and separate carbon powder; Grind the shell material into powder of 100-200 mesh, mix it with the overhaul slag after flotation, and acid leaching. The mixing ratio of shell material to overhaul slag is 1: (0-2); S2, mixing the mixed raw material with the second solution to prepare a slurry, wherein the mass volume ratio of the raw material to the second solution is 1:(1-3), then, adding 4%-10% of a leaching aid, a cyanide destroying agent and a leaching agent by mass ratio, maintaining the system pH at 0.5-1.5, and stirring the reaction at 70°C-100°C for 1-4 hours; S3, after the end of S2, the fourth solid material is pumped in, and the ratio of the fourth solid material to the mixture of the shell material and the overhaul slag is (0.1-0.3) by mass ratio: 1, the pH is adjusted to 2-4, and after stabilization for 30-60 minutes, the slurry is filtered to obtain a first filtrate and a first filter residue; If the lithium content of the first filter residue is less than 0.1%, the step S4 is omitted; S4, the first filtrate is subjected to secondary leaching with the third solution, the liquid-to-solid ratio is controlled to be 1.5-3:1 by mass ratio, the pH is adjusted to 1-2 by industrial hydrochloric acid or sulfuric acid, the reaction is carried out at 50°C-80°C for 1h-2h, and the second filtrate and the second filter residue are obtained by filter pressing; S5, adjusting and stirring the second filter residue with the fifth solution, controlling the liquid-to-solid ratio to be 1.5-3:1 by mass ratio, washing at room temperature for 30-60 minutes, and obtaining a third filtrate and a third filter residue after filter pressing; S6. Mix the third filter residue, aggregate and adhesive in a mass ratio of 100:5~20:1~5, and prepare a slag-removing agent product after ball pressing and drying.

2. A method for extracting lithium from shell material and overhaul slag and co-producing slag-removing agent for steel mills according to claim 1, characterized in that: Also includes: S7, adding the first filtrate and alkali solution into a decontamination tank, controlling the pH value to 5-8 and the temperature to 40°C-80°C, so that the impurity elements in the solution are precipitated, stirring the reaction for 1h and filtering to obtain a fourth filtrate and a fourth filter residue; S8. Use liquid alkali to completely dissolve the sixth solid material and / or aluminum hydroxide to obtain a sodium aluminate solution, and use hydrochloric acid or sulfuric acid and / or aluminum hydroxide to completely dissolve to obtain an aluminum chloride solution or an aluminum sulfate solution; add the sodium aluminate solution and the aluminum chloride solution or the aluminum sulfate solution to the fourth filtrate, control the pH value during the process to 9-10, control the endpoint pH value to 6-8, and the temperature to 80°C-100°C. After stabilizing for 1h-3h, filter by pressure to obtain a fifth filtrate and a fifth filter residue; the fifth filter residue is a lithium-rich residue with a lithium content greater than 4%.

3. The method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel plant according to claim 2, characterized in that: Also includes: S9. The fifth filter residue is slurried with pure water to a liquid-to-solid ratio of 10-30:1, and is subjected to high temperature and high pressure analysis at 200°C-250°C for 1h-3h. After filtration, a sixth filtrate and a sixth filter residue are obtained. The sixth filter residue and pure water are subjected to multi-stage plate exchange and circulating water cooling, and a lithium-rich concentrate is obtained after membrane concentration, which is then synthesized to obtain industrial-grade lithium carbonate.

4. The method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel plant according to claim 1, characterized in that: In S1, the mixing ratio of the ground flour shell material and the overhaul slag after flotation is, by mass ratio, fluorine is greater than 26% to 36% and carbon is 5% to 15% after mixing; When the carbon content in the ground flour shell material and the overhaul slag after flotation is less than 15%, the overhaul slag does not need to be flotated to separate the carbon powder.

5. The method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel plant according to claim 4, characterized in that: The flotation agent is a general term for foaming agent, inhibitor and collector; the foaming agent is No. 2 oil or ether alcohol; the inhibitor is water glass; and the collector is kerosene.

6. The method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel mill according to claim 1, characterized in that: In S2, The leaching aid is aluminum oxide or aluminum hydroxide. After the leaching aid is added, the molar ratio of fluorine to aluminum in the mixed slurry is controlled between 2 and 3:1; The leaching agent is industrial hydrochloric acid or sulfuric acid; If the cyanide-breaking agent is a hydrochloric acid system, sodium chlorate or sodium hypochlorite is selected; if the cyanide-breaking agent is a sulfuric acid system, hydrogen peroxide is selected. The addition ratio is 0-2% of the weight of the shell material and overhaul slag, and cyanide is converted into non-toxic nitrogen and carbon dioxide.

7. The method for extracting lithium from flour shell material and overhaul slag and co-producing slag-removing agent for steel mill according to claim 4, characterized in that: When N is 1, The second solution and the third solution are tap water; the fifth solution is tap water; The first solid material is not added; the sixth solid material is aluminum hydroxide; When N is greater than 1, The second solution is the second filtrate; the third solution is the third filtrate; the fifth solution is the fifth filtrate; The fourth solid material is the fourth filter residue; the sixth solid material is the sixth filter residue.

Citation Information

Patent Citations

  • Harmless electrolytic aluminum overhaul slag, application of harmless electrolytic aluminum overhaul slag and harmless method for electrolytic aluminum overhaul slag

    CN115846377A

  • Treatment method of electrolytic aluminum carbon residues

    CN118125481A

  • Method for recycling mixed material dreg of overhauling groove slag of electrolytic cell

    CN102989744A

  • Method for producing converter slugging agent through electrolytic aluminum overhaul slag

    CN109735678A

  • Method for extracting lithium from alumina production process and preparing battery-grade lithium carbonate

    CN110627095A